Berberine inhibits liver damage in rats with non-alcoholic fatty liver disease by regulating TLR4/MyD88/NF-κB pathway - Wang, Lingling; Jia, Zhandong; Wang, Bangcai; Zhang, Bin (Turkish Journal of Gastroenterology, 2020)
Background/Aims: This study aimed to explore the therapeutic effects and underlying mechanism of berberine (BBR) on the non-alcoholic fatty liver disease (NAFLD) induced by high-fat diet (HFD). Materials and Methods: Rats were randomly divided into the following 4 groups: control (normal diet), model (HFD), polyene phosphatidylcholine HFD+PPC, and BBR (HFD+BBR) group. The NAFLD models were prepared by feeding with HFD for 12 weeks. The liver tissues were observed by oil red O staining. H&E staining was used to detect pathological changes in the liver tissues. Serum levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), total cholesterol (TC), triglyceride (TG), low-density lipoprotein cholesterol (LDL-C), and high-density lipoprotein cholesterol (HDL-C) were detected by an automatic biochemical analyzer. ELISA was performed to observe the inflammatory cytokines (TNF-α, IL-6, and IL-1β) expressions. The levels of TLR4, MyD88, and NF-κB p65 were analyzed using western blot and qRT-PCR, respectively. The nuclear translocation levels of NF-κB in the primary liver cells were measured using flow cytometry. Results: BBR could significantly alleviate the liver tissue steatosis and inflammatory cell infiltration; reduce the NAFLD activity scores and serum levels of ALT, AST, TC, and LDL-C; decrease the levels of TNF-α, IL-6, and IL-1β, and reduce the expression of TLR4, MyD88, and NF-κB in the liver tissues. BBR could also reverse the nuclear translocation of NF-κB in the primary liver cells. Conclusion: BBR alleviated the progress of NAFLD and liver damage, which might contribute to inhibit the nuclear translocation of NF-κB via the TLR4/MyD88/NF-κB pathway.